Clinical epidemiology of venous thromboembolic disease: An institutional registry - AlSheef, Mohammed; Alshammari, Fouad Taiwilaa; Alhawish, Mashel khalid; Alghamdi, Abduljabar Ghazi; Alqudhybi, Abdullah Fahad; Abu-Shaheen, Amani (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Venous thromboembolism (VTE) is a major health concern, with an annual incidence of approximately 1 in 1000. The epidemiology of VTE in Saudi Arabia has not been adequately described yet. Therefore, this study aimed to assess the clinical characteristics, risk factors, diagnostic methods, management, and clinical outcomes of patients with VTE. Methods: This study was based on a VTE registry created over ten years at King Fahad Medical City (KFMC) in Riyadh, Saudi Arabia. All adult inpatients and outpatients referred to the thrombosis unit of the KFMC with clinically suspected VTE (including pulmonary embolism (PE) and deep vein thrombosis (DVT) were enrolled. Data were collected using a standardized case report form, which included demographic and clinical characteristics, risk factors, diagnostic methods, management, and outcomes. Results: A total of 1008 patients were recruited. Most patients were women (73.2%), and more than half of all patients had unprovoked VTE (58%). Among the provoked cases, the most frequent cause was surgery (29.8%), followed by hospitalization (24.2%). There was a significant statistical association between provoked status and sex, family history of VTE, smoking, recent hospitalization within 3 months for a medical condition, the site of VTE, and underlying peripheral vascular disease and varicose veins (all p < 0.05). The majority (88.3%) of patients with deep vein thrombosis was hospitalized for ≤3 days (n = 433, 79.9%), while fewer than half of the patients with PE needed hospitalization (45.3%). Thrombolytic therapy was administered to 14.1% (n = 142) of patients, and catheter-directed thrombolysis was performed in 1.0% (n = 10) of patients. The odds of mortality for provoked VTE were 3.20 times higher than those of unprovoked VTE [2.12 – 4.83; p-value < 0.001]. Conclusion: Unprovoked VTE was more common than provoked VTE in the Saudi Arabian cohort, implying hereditary predisposition. Furthermore, male sex, family history of VTE, prior history of VTE, type of VTE, underlying obesity, history of trauma, surgery, hospitalization, pregnancy, and 3–6 months of anticoagulation therapy were the most critical risk factors for VTE recurrence. The treatment patterns and clinical results were comparable to those reported in the literature.